Behavior prediction of reinforced concrete beams shear strengthened with CFRP - Borges Soares, Palloma; Manica Lazzari , Paula; Campos Filho, Américo; Manica Lazzari, Bruna (Revista ALCONPAT, 2024)
This work presents the computational modeling of reinforced concrete beams, strengthened to shear with carbon fiber-reinforced polymers (CFRP), using the finite element method (FEM) and the customized ANSYS software, version 19.2. It is important to emphasize that contact elements and bilinear cohesive zone models provided by ANSYS were used to model the concrete-reinforcement interface. These models were used to identify the modes of premature failure caused by the debonding of the reinforcement, which causes poor use of the CFRP’s resistance properties. The structural elements used in this analysis were twelve simply supported reinforced concrete beams, without and with shear reinforcement using CFRP, which were experimentally tested by Khalifa (1999). From the analysis of the results, it was observed that the developed numerical models were able to accurately predict the behavior of the simulated beams, both in terms of load-displacement, as well as the load and rupture mode of the beams.